"Oh, the Places You Can Go" Gen Z Psychology Students' Perceived Career Options and Interests. (July 2022) - Collisson, Brian; Eck, Brian E.
Background: Career options available to psychology graduates are often underestimated despite psychology being a marketable and versatile degree with hundreds of career options. Objective: This article identifies which career options students perceive as available to psychology graduates and assesses student interest in psychology-related careers. Method: In Study 1, 12 focus groups consisting of 59 psychology majors were asked to list the career options available to psychology graduates. In Study 2, 430 psychology students rated their interest in 273 psychology-related careers. Results: Study 1 revealed careers perceived as available to psychology graduates were most often in counseling (92%) and applied-settings (50%) with child-related (42%), business (25%), and research (25%) careers listed less often. Study 2 revealed psychology majors were most interested in counseling and child-related careers, with 18 of their top 20 careers of interest involving mental health or working with children. Conclusion: Students are often unaware of career options in psychology beyond counseling. Consequently, they tend to be most interested in careers related to counseling and children, particularly careers involving the mental healthcare of children. Teaching Implications: Findings may encourage psychology departments to communicate the broad range of psychology career options for the recruitment and advising of psychology majors.